Biological interactions of biocompatible and water-dispersed MoS2 nanosheets with bacteria and human cells. Issue 1 (December 2018) - Kaur, Jasneet; Singh, Manjot; Dell'Aversana, Carmela; Benedetti, Rosaria; Giardina, Paola; Rossi, Manuela; Valadan, Mohammadhassan; Vergara, Alessandro; Cutarelli, Anna; Montone, Angela; Altucci, Lucia; Corrado, Federica; et al.
Abstract Two dimensional materials beyond graphene such as MoS2 and WS2 are novel and interesting class of materials whose unique physico-chemical properties can be exploited in applications ranging from leading edge nanoelectronics to the frontiers between biomedicine and biotechnology. To unravel the potential of TMD crystals in biomedicine, control over their production through green and scalable routes in biocompatible solvents is critically important. Furthermore, considering multiple applications of eco-friendly 2D dispersions and their potential impact onto live matter, their toxicity and antimicrobial activity still remain an open issue. Herein, we focus on the current demands of 2D TMDs and produce high-quality, few-layered and defect-free MoS2 nanosheets, exfoliated and dispersed in pure water, stabilized up to three weeks. Hence, we studied the impact of this material on human cells by investigating its interactions with three cell lines: two tumoral, MCF7 (breast cancer) and U937 (leukemia), and one normal, HaCaT (epithelium). We observed novel and intriguing results, exhibiting evident cytotoxic effect induced in the tumor cell lines, absent in the normal cells in the tested conditions. The antibacterial action of MoS2 nanosheets is then investigated against a very dangerous gram negative bacterium, such as two types ofSalmonellas : ATCC 14028 and wild-typeSalmonella typhimurium . Additionally, concentration and layer-dependent modulation of cytotoxic effect is found both on human cells andSalmonellas .